Pharmacokinetics of a New Neuroprotector — Indenoquinoxalinone Derivative after Intravenous Administration in Rabbits and Rats; Bulletin of Experimental Biology and Medicine; Vol. 175, iss. 6 - Yanovskaya E. A. Elena Anatoljevna; Frelikh G. A. Galina Andreevna; Lakeev A. P. Aleksandr Pavlovich; Chernysheva G. A. Galina Anatoljevna; Smolyakova V. I. Vera Ivanovna; Kovrizhina A. R. Anastasia Ruslanovna (2023, 2023)
Title screen